2000
DOI: 10.1128/iai.68.1.320-327.2000
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and Extracellular Cytokine Production by Human Mixed Mononuclear Cells in Response to Group B Streptococci

Abstract: Group B streptococci (GBS) are a major cause of severe infection in newborns, pregnant females, and other immunocompromised hosts. Infection often includes septicemia, shock, pneumonia, and respiratory failure. In previous studies, we have reported that GBS induce marked production of tumor necrosis factor alpha (TNF-␣) by human mononuclear cells. The present study was designed to measure the production of TNF-␣ as well as additional cytokines, including interleukin 1␤ (IL-1␤), IL-6, IL-8, IL-12, and gamma int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 27 publications
0
38
0
1
Order By: Relevance
“…NF-B p65 translocation occurs within minutes of extracellular stimulation, and subsequent intracellular protein accumulation follows within 30 -60 min (26). Typically, intracellular proteins appear before or simultaneously with extracellular protein (38). Thus the appearance of circulating TNF-␣ in our subjects (68) before intracellular accumulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NF-B p65 translocation occurs within minutes of extracellular stimulation, and subsequent intracellular protein accumulation follows within 30 -60 min (26). Typically, intracellular proteins appear before or simultaneously with extracellular protein (38). Thus the appearance of circulating TNF-␣ in our subjects (68) before intracellular accumulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The increased incidence of invasive disease due to GBS in the newborn is due to frequent exposure to the organism (approximately 25% of women are colonized with GBS) in the context of specific deficiencies of neonatal host defense-particularly the diminished production and delivery of neutrophils to the site of infection and the frequent lack of specific antibody against the infecting serotype (5-7). Neonatal monocytes and macrophages are also impaired compared with macrophages from older children and adults, but are capable of producing large amounts of inflammatory mediators such as TNF in response to GBS (8,9). It is likely that excessive production of inflammatory mediators, including TNF and NO, contributes to the severity of sepsis and meningitis due to GBS, though the role of exuberant or unbalanced production of proinflammatory mediators in the pathogenesis of sepsis remains controversial (10).…”
mentioning
confidence: 99%
“…In accordance with this, it has been suggested that IFN-␥ produced by the NK or T cell is of importance in the host defense against S. pneumonia (23). In vitro experiments have shown that Streptococcus pyogenes strains induce production of IFN-␥ (type 1 response), but only weakly induce production of IL-4 (16,18). Furthermore, IFN-␥ rather than IL-4 is the dominant cytokine elicited in tonsils in vivo (1).…”
mentioning
confidence: 99%